Recent advances in methanogenesis through direct interspecies electron transfer via conductive materials: A molecular microbiological perspective. (February 2021) - Kang, Hyun-Jin; Lee, Sang-Hoon; Lim, Tae-Guen; Park, Jeong-Hoon; Kim, Boram; Buffière, Pierre; Park, Hee-Deung
Graphical abstract: Highlights: DIET for methanogenesis is critically reviewed in view of molecular microbiology. Metabolic syntrophy between exo- and endo -electrogens is important in the DIET. Molecular microbiological methods revealed candidate microorganisms in DIET. Meta-omics approaches can elucidate DIET microorganisms and their functional role. Abstract: Conductive materials can serve as biocatalysts during direct interspecies electron transfer for methanogenesis in anaerobic reactors. However, the mechanism promoting direct interspecies electron transfer in anaerobic reactors, particularly under environments in which diverse substrates and microorganisms coexist, remains to be elucidated from a scientific or an engineering point of view. Currently, many molecular microbiological approaches are employed to understand the fundamentals of this phenomenon. Here, the direct interspecies electron transfer mechanisms and relevant microorganisms identified to date using molecular microbiological methods were critically reviewed. Moreover, molecular microbiological methods for direct interspecies electron transfer used in previous studies and important findings thus revealed were analyzed. This review will help us better understand the phenomena of direct interspecies electron transfer using conductive materials and offer a framework for future molecular microbiological studies.